A dendroclimatic analysis of Nothofagus betuloides forests from Cordillera Darwin, Tierra del Fuego, Chile - Soto-Rogel, Pamela; Aravena Donaire, Juan Carlos (My University, 2017)
The lack of long and complete instrumental records hampers the study of climatic variability in remote regions of the Earth. Alternatively, paleoenvironmental sources of information such as tree rings provide valuable information on climate variations. In the context of this study, four new tree-ring width chronologies were developed from Nothofagus betuloides in Cordillera Darwin, southern Chile. The main goal of this study is to estimate the influence of the Antarctic Oscillation (AAO) and changes in temperature and rainfall on Nothofagus betuloides tree growth. New tree-ring chronologies were developed from samples collected at Glaciar Schiaparelli valley (54 degrees 25' S, 70 degrees 54' W) and Valle de los Divorcios (54 degrees 36' S, 69 degrees 03' W). Four already published tree-ring width chronologies from Nothofagus betuloides in the region were also included in the analysis. Using Principal Component Analysis (PCA) on the eight tree-ring width chronologies, two main growth patterns were identified: PC1 or eastern tree-growth mode, and PC2 or western tree-growth mode. Both components showed significant correlations with air temperature and AAO. PC1 presented significant negative correlations with summer rainfall, temperature and AAO index. On the contrary, PC2 showed significant positive correlations with air temperatures, rainfall and AAO index. Significant growth responses to climate variability indicate that N. betuliodes records could be considered a reliable proxy of environmental fluctuations during the last few centuries in Cordillera Darwin, Chile.
Keywords: nothofagus betuloides; rainfall; temperature; aao; cordillera de darwin